Molecule Formats of B-Cell Targeting Biologics: Applications in Autoimmune Disease Treatment and Impacts on Manufacturability - Yueming Qian; Tamer I. Mahmoud (Pharmaceutics)
The targeting of B-lymphocyte cells has emerged as one of the most pivotal strategies in the management of autoimmune diseases. This review provides an overview of protein therapeutics illustrating their direct and indirect effects on B-cells using different molecule formats. The design and format of these molecules influence their mode of action and affect their manufacturing strategies. Manufacturability should be assessed at an early stage and continuously through collaboration between discovery and development teams. Scalability evaluations should encompass not only process development and facility compatibility but also cell line development. Examples of format-specific manufacturability of biologics are reviewed to offer general insights into enhancing productivity and quality in a cost-effective manner.